Adaptive shifts in Neotropical planthoppers: new troglobitic species and the first surface species of Ferricixius Hoch & Ferreira, 2012 (Hemiptera: Fulgoromorpha: Cixiidae) from Brazilian caves - Santos, Júlio César Do Carmo Vaz; Hoch, Hannelore; Zampaulo, Robson De Almeida; Simões, Matheus Henrique; Ferreira, Rodrigo Lopes (Zootaxa, 2023)
Here we describe three cixiid species new to science which we assign to the hitherto monotypic genus Ferricixius Hoch & Ferreira, 2012 from Brazil. Ferricixius michaeli sp. nov. and F. goliathi sp. nov. of the new species are—like the type species Ferricixius davidi Hoch &Ferreira, 2012—obligately cavernicolous and display varying degrees of troglomorphy, such as the reduction of compound eyes, wings, and bodily pigmentation, while F. urieli sp. nov. displays well developed compound eyes and wings, and—although so far only found inside caves—is ecologically classified as either epigean, or subtroglophile. We provide a modified diagnosis for the genus and an identification key to the species of Ferricixius, as well as information on the distribution, ecology, and habitat of the three new species herein described. Evolutionary implications are discussed, and adaptive shifts from epigean to subterranean habitat are presumed to be the most likely scenario underlying the evolution of cave dwelling Ferricixius.